Congenital bile duct cystic dilatations (part 2). Extrahepatic bile duct - Nari, Gustavo; López, Alesio E.; Joseph, Ángel; Ortega, Elías; De Elias, M. Eugenia; López, Flavia (Revista Argentina de Cirugía, 2026)
Congenital dilatation of extrahepatic bile ducts is rare in the Western countries and is more common in children than in adults. The diagnosis requires high level of suspicion and is made by cholangiography tests, among which MRCP is the most useful nowadays. Malignant transformation of these cystic dilatations is well-known; therefore, complete resection of the cystic pouch is mandatory